Islamic horror films and adolescents’ religious behaviour: A study in Sukabumi - Suherman, Muhammad Tanziil; Pujiastuti, Yanti Lestari; Juliansyah, Aris; effendie, Itsna Nurhayat; Meigawati, Dine (Universitas Padjadjaran, 2026)
Background: Horror films with islamic religious themes in recent years have become an increasingly popular phenomenon. Islamic religious horror film in their frames contain elements that are related to islamic teaching and religious concept. Some previous study have examined the impact of islamic religious film on social change in society, but previous studies have not coveres in depth how the influence of isamic religious horror film on religious behaviour. Purpose: the purpose of this study is to determine whther ther is an influence between islamic religious film on islamic religious behaviour. Methods: This research uses quantitative methods, path analysis and the theory is cultivation theory. Results: The result of this study indicate that there is a significant influence between watching Islamic religious horror films and the religious behaviour of high school students, with the content of the message being the most dominant factor influencing religious behaviour. Conclusion: The content of horror film is the most influential factor on students religious behaviour. Beliefs (akidah) are the most influenced by horror films. And the intensity of viewing does not always have an impact on all aspects of religion. Implications: This study shows that Islamic religious films have a complex and varied influence on religious behavior. In general, they have an influence mainly on aspects of belief and worship practices. This needs to be taken into consideration in film production, especially films with religious themes.